Nitrogen Analysis in Legume and Nonlegume Plants - Angelia, Cut Wulan; Maghfirah, Ruhul; Purnama, Agnia; Farida, Mutia; Afifi, Muhammad Ridho; Siregar, Indri Hastuti (JURNAL BIOLOGICA SAMUDRA, 2025)
Nitrogen is one of the essential macronutrients required by plants. It can be obtained from both organic and inorganic fertilizers. Naturally, plants acquire nitrogen through the nitrogen-fixation process carried out by Rhizobium bacteria, which occurs exclusively in leguminous plants. This study aims to evaluate the differences in nitrogen content between legume and non-legume plants. The Kjeldahl method was used to measure total nitrogen in peanut (Arachis hypogaea L.), butterfly pea (Clitoria ternatea L.), and maize (Zea mays). The results showed that legume plants—peanut and butterfly pea—contained higher nitrogen levels than the non-legume plant, maize, with values of 6.82%, 5.06%, and 4.42%, respectively. Therefore, it can be concluded that legume plants have a greater capacity for nitrogen uptake due to biological fixation in their root nodules, making them a potential natural nitrogen source for improving soil fertility.